2020
DOI: 10.1108/arj-09-2020-0285
|View full text |Cite
|
Sign up to set email alerts
|

Preparing graduates with the employability skills for the unknown future: reflection on assessment practice during COVID-19

Abstract: Purpose The purpose of this paper is to provide an authentic and relevant way of sharing our realisation of the significance of integrating employability skills in assessment practice. This is supported from the anecdotal evidence received from students, which show that the inclusion and assessment of employability skills has provided them with an artifact that demonstrates the employability skills required for the continually changing future and workplace. For staff, the ability to assess and give feedback on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…One is that instructors are one of the avenues of research identified in the emergent literature (Sangster et al, 2020, p. 446). The second is that instructors are less studied than student experiences (Ali et al, 2020;Bowyer, 2021;Dyki et al, 2021;Malan, 2020;Pasion et al, 2021;Ramachandra and Wells, 2021). Furthermore, the Sangster et al ( 2020) study looks at 45 countries but greatly compressed the space available for lessons learned (Fogarty, 2020, p. 563).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One is that instructors are one of the avenues of research identified in the emergent literature (Sangster et al, 2020, p. 446). The second is that instructors are less studied than student experiences (Ali et al, 2020;Bowyer, 2021;Dyki et al, 2021;Malan, 2020;Pasion et al, 2021;Ramachandra and Wells, 2021). Furthermore, the Sangster et al ( 2020) study looks at 45 countries but greatly compressed the space available for lessons learned (Fogarty, 2020, p. 563).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging literature on accounting education in the COVID-19 context has focussed on faculty autoethnography and undergraduate students studies. The group of articles on faculty describes recent teaching experiences (Ackerman, 2021;Beatson et al, 2021;G omez and Alba, 2021;Haynes, 2020;Mai, 2020;Powell and McGuigan, 2020;Stewart and Khan, 2021;Wong and Zhang, 2020) whilst the other group highlights student responses and challenges (Ali et al, 2020;Bowyer, 2021;Dyki et al, 2021;Malan, 2020;Pasion et al, 2021;Reyneke et al, 2020). There is also a paper on graduate students (Ramachandra and Wells, 2021) and another one on the training of instructors for online education (Sadiq, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, teaching the current COVID-19 situation to accounting students within the ethics content is more fragmented than ever before as it may help focus the fragmentation and ground the information on credible sources. Previous evidence (Bowyer, 2021) emphasises the importance of teaching historical events, especially within the economic sciences; therefore, teaching the current COVID-19 situation would enhance students' employability skills for unknown future events (Dyki et al, 2021) and their ability to make future ethical decisions.…”
Section: Summary Of Results Discussion and Future Avenuesmentioning
confidence: 99%
“…The youth unemployment rate in Hong Kong faced a 5-year record low from 5.6% on average in 2015 to 9.8% in 2020 (Trading Economics, 2020). Young graduates face tough competition and low salaries as they enter Hong Kong's crowded workforce, especially during the period of economic crisis, such as the pandemic COVID-19 (Kamaruddin et al , 2020; Dyki et al , 2020; Ma and Bennet, 2021). While the global economic situation remains weak, the local labor market in Hong Kong deteriorated during the third quarter of 2020 under the pandemic, in which unemployment and underemployed are more common in many affected sectors, such as consumption, tourism-related industries, food and beverage services, entertainment and recreation sectors (Census and Statistics Department, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%